Uncovering Income Class Heterogeneity in Self-Reported Anxiety Levels Among Indonesians Before and During the COVID-19 Pandemic - Indera Ratna Irawati Pattinasarany (Asian Journal for Public Opinion Research)
This study investigates the variation in anxiety levels across income classes in the wake of the COVID-19 pandemic in Indonesia. The research is based on data from nationally representative surveys conducted in 2017 and 2021, and it employs a multilevel mixed-effects ordered logistic model. The unique aspect of this investigation lies in its utilization of the Cantril ladder, a commonly employed tool in public opinion research, to gauge anxiety levels. Participants are prompted to assess their present life circumstances concerning their daily worries and anxieties. The empirical findings provide evidence that individuals in provinces with higher exposures to COVID-19 reported heightened anxiety levels. Furthermore, the results highlight a consistent association between higher household income and lower levels of anxiety. Notably, individuals from the highest income group experienced a substantial decline in anxiety levels during the pandemic. When examining specific income classes, the study reveals heightened anxiety among women in higher-income brackets and among lower-income households residing in urban areas. Furthermore, regarding macroeconomic circumstances, the results illustrate a positive correlation between economic prosperity and anxiety levels among members of low-income households. The study also uncovers a positive connection between income inequality and self-assessed anxiety within upper-middle and high-income brackets.